2016
DOI: 10.5057/ijae.ijae-d-15-00048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colored Overlays on Reading Comfort in People with and without Meares-Irlen Syndrome

Abstract: People with Meares-Irlen syndrome (MIS) perceive visual distortions and abnormal brightness in text. Translucent colored overlays may alleviate these symptoms, making reading more comfortable. We examined various colors' effect on reading comfort, and whether colored overlays affect reading in Japanese participants with and without possible MIS. Participants read Japanese syllabary (Hiragana) and English alphabets with ten colored overlays (purple, rose, peach, orange, yellow, green, light blue, blue, blue-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…From this study, it is disclosed that by using the blue colour overlays, the reading score of the subject has increased. The finding parallels with the previous research by Imaizumi et al (2016), which emphasises that bluish colour overlays make reading more comfortable to the participants with and without symptoms of Irlen syndrome compared to other colours in the Japanese syllabary and also English alphabets condition.…”
Section: A Reading Scoresupporting
confidence: 89%
See 2 more Smart Citations
“…From this study, it is disclosed that by using the blue colour overlays, the reading score of the subject has increased. The finding parallels with the previous research by Imaizumi et al (2016), which emphasises that bluish colour overlays make reading more comfortable to the participants with and without symptoms of Irlen syndrome compared to other colours in the Japanese syllabary and also English alphabets condition.…”
Section: A Reading Scoresupporting
confidence: 89%
“…A study by Ikeshita et al (2018) identifies that the blue band can positively affect children with dyslexia because they can read more efficiently when the digital text is highlighted with a blue band. Besides, a study conducted by Imaizumi et al (2016) found that using the bluish colour overlays can make the reading more comfortable for the participants with and without Irlen Syndrome in the Japanese syllabary as well as English alphabets condition. Apart from that, the blue colour overlay also can increase reading achievement, especially for individuals who suffer from the symptoms of Irlen Syndrome (Imaizumi et.…”
Section: Research Done Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Affective engineering (e.g., [1,2]) and psychophysiological (e.g., [3]) studies have sought to investigate aspects of human vision, including visual acuity and color perception. Some individuals have visual disturbances due not only to injury and disease but also to aging (e.g., senile cataract).…”
Section: Introductionmentioning
confidence: 99%